STUDI LITERATUR ANALISIS PENGGUNAAN APLIKASI SOCRATIVE SEBAGAI ALAT EVALUASI PEMBELAJARAN - Saccani, Ariya; Rahma Sudarni, Ajeng; Ekarini, Fitria (ADIDAYA : Aplikasi Pendidikan dan Sosial Budaya, 2026)
This study aims to analyze the use of the Socrative application as an online assessment tool in the context of digital learning. This literature review examines national studies from 2021–2025 that discuss Socrative’s role in formative and summative assessments, its impact on learning outcomes, and its effectiveness in increasing student engagement. The reviewed studies indicate that Socrative provides real-time feedback, automatic scoring, interactive quiz formats, and flexible access across devices, making it a practical and efficient tool for digital classroom assessment. The analysis also shows that Socrative contributes to improving students’ conceptual understanding and motivation, particularly when used in game-based or student-centered evaluation models. However, limitations remain, including its inability to assess complex analytical responses and the dependency on stable internet access. The findings suggest that Socrative is highly suitable for formative assessment and digital learning environments, although further research is needed to explore its use in higher-order evaluation. This study contributes to a comprehensive understanding of Socrative’s pedagogical benefits and challenges within contemporary digital education.